HDPE/mesoporous silica nanocomposites by in-situ polymerisation: structural details and mechanical response - Bento, A. (2012)
Mesoporous silicas exhibit stable three-dimensional structures, made of ordered channels with well-defined geometries and dimensions at nanometer scale, able to host intercalation reactions.